Acceptability of PGDAEM Distance Program Among Extension professionals in India - Kumari, Veenita; Kameswari, S. L.; Modi, Ragini (Journal of Agricultural Extension Management, 2024)
Distance education, or distance learning, is an educational approach that relies on the Information technology, and instructional systems that plan to provide learning to students who are physically not present in a class room setting. Instead of attending courses personally, teachers and students communicate at times of their convenience and choosing and exchange printed or electronic materials through any suitable technology.Distance education is becoming more and more demanding in the recent times as the latest techniques and technologies can be easily spread to the farthest part of the world easily and connect between organizations as well as the universities to collaborate in different fields. Distance learning will remain as part of e-learning , web based learning through virtual classrooms and digital teamwork, where contents will continue to bedelivered through internet, audio, video tape, and conferencing through video; satellite and etc.  The National Institute of Agricultural Extension Management (MANAGE) established in 1987, is an apex level autonomous institute under the Ministry of Agriculture & Farmers Welfare, Government of India. MANAGE is the Indian response to challenges of agricultural extension in a rapidly growing and diverse agriculture sector. Realizing the paramount importance of public and private extension system, MANAGE has launched a one-year Post-Graduate Diploma in Agricultural Extension Management (PGDAEM) in distance learning mode during 2007, under the Centrally Sponsored Scheme “Support to State Extension Programme for Extension Reforms.” This study conducts, a feedback analysis to assess the effectiveness and the constraints faced by the SAMETIs and candidates in the PGDAEM Program. The study employed a detailed survey designed as an appropriate tool to generate the vital facts of the people under study. Conducted online and data was collected online by inviting educators to fill the online questionnaire, irrespective of the geographical location. A set of questions were posted in Google form on issues such as the admission procedure, course fee, funds to the SAMETIs, sponsorship, assignments, project work, examinations, study material, evaluation, backlog policy, medium of instruction, monitoring process, honorarium to resource persons and coordinator, lodging and boarding, institutional charges and suggestions for improvements. As a result, it was found that the respondents expressed that PGDAEM Program is very useful for them to improve their skills in latest extension technologies and techniques in their field situation where they are working. They express and suggest that they need the study material in the colloquial languages, more number of classes for orientation about the program and time for contact classes. They opine that they require update of the latest knowledge time to time which is helped through PGDAEM. They feel only that the busy work schedule is a limitation for them to pursue PGDAEM Program.